Assessment of water pollution in Khun Thale swamp - Sridang, Porntip; Danteravanich, Somtip; Thananuphaphphaisarn, Suwat; Durand, Charlotte (Asia-Pacific Journal of Science and Technology, 2017)
The Khun Thale swamp is an integral part of the Tapi River’s catchment area and its geographical location is a small lake. The swamp is located in the lower part of the Tapi river. The average depth of the swamp is 2.2 meters and it covers an area of about 2.03 km2 . The local authorities and the provincial government have planned to develop this swamp as a site for tourism in Surat Thani province. Since the environmental scientific information of this swamp has not been updated, this study was carried out in order to assess water quality, identify the pollution sources as well as to determine the biodiversity of this ecosystem. This information brings understanding of the existing ecosystem of the Khun Thale swamp and its water pollution condition. The study implies that the Khun Thale swamp has been polluted from many sources. It was found that around 30 factories contribute to the swamp’s pollution. Domestic wastewater and potential sources of agricultural pollution discharge were identified and described. From the biodiversity information, 47 genera within 3 divisions of phytoplankton and 21 genera of zooplankton were found in this swamp. It also found that 60, 44 and 41 genera of aquatic animals, plants, and birds were determined in this area, respectively. These reflected the Khun Thale swamp as a place of environmental richness in Surat Thani province, and it should be protected. In addition, suggestions and alternative approaches for sustainable water pollution management of the Khun Thale swamp were also addressed.